Dimensionnement et Gestion de l’Energie au Sein d’un Système Hybride de Production d’Energie - Bi, Bati Ernest Boya; Gbaha, Prosper; Koua, Kamenan Blaise; Koffi, Magloire Paul Ekoun (European Scientific Journal, ESJ, 2018)
Renewables Energies, allowing decentralized electricity production, can help to solve the problem of electrification of isolated sites where a large number of people are devoid of any energy supply. This article aims at sizing and studying the management of energy flows in a hybrid multi-source system. The energy management strategy is an algorithm that determines at each moment the sharing of power between the various components of the system. The dimensioning allowed to obtain a good overall operation and to limit the cost of the installation. The sizing tools also allowed to define the solar power and storage volume needed to meet the demand of the given load. The strategy that we present in this article is a technique of optimized management of the energy of the hybrid system studied in order to limit the losses of conversion. This strategy reduces the size of the various components such as the PV field, the battery pack, the electrolyser and the fuel cell as well as the production costs.